Quality of life and colorectal cancer: a review - Jeff Dunn; Brigid Lynch; Joanne Aitken; Barbara Leggett; Kenneth Pakenham; Beth Newman (Australian and New Zealand Journal of Public Health, 2003)
Abstract Objectives: To describe what is known of quality of life for colorectal cancer patients, to review what has been done in the Australian setting and to identify emerging directions for future research to address current gaps in knowledge. Method: A literature search (using Medline, Psych Info, CINAHL and Sociological Abstracts) was conducted and 41 articles identified for review. Results: Three key areas relating to quality of life in colorectal cancer patients emerged from the literature review: the definition and measurement of quality of life; predictors of quality of life; and the relationship of quality of life to survival. Results of existing studies are inconsistent in relation to quality of life overtime and its relationship to survival. Small sample sizes and methodological limitations make interpretation difficult. Conclusions: There is a need for large‐scale, longitudinal, population‐based studies describing the quality of life experienced by colorectal cancer patients and its determinants. Measurement and simultaneous adjustment for potential confounding factors would productively advance knowledge in this area, as would an analysis of the economic cost of morbidity to the community and an assessment of the cost effectiveness of proposed interventions. Implications: As the Australian population ages, the prevalence of colorectal cancer within the community will increase. This burden of disease presents as a priority area for public health research. An improved understanding of quality of life and its predictors will inform the development and design of supportive interventions for those affected by the disease.